Exploring the Effect of Disruptive Behavioral Disorders on Quality of Learning Among School Children: Across-sectional Study (Journal of Forensic Medicine & Toxicology, 2025)
Background: disruptive behavioral disorders among primary school children is oone of the most popular, which has  negative social, psychological, educational, and physical repercussions on children and families. Objective: This study sought to determine effect disruptive behavioral disorders quality of learning among school chil dren. Methods: A descriptive cross-sectional design study was conducted at Baquba primary schools in Diyala Governorate,  and the study period was extended from October 6th, 2024, to January 15th, 2025. A nonprobability purposive sample was  used to include 275 teachers working at selected Baquba primary schools, Iraq. Data were collected using a self-admin istered questionnaire, two components of the study instruments. Initially, the demographic sheet contained the individ uals’ sociodemographic data. An explicit children’s emotional and behavioral problems scale is included in the second  section. The collected data were analysed using SPSS version 26. Results: The results showed that areas were within a moderate disruptive behavior level for: aggression, hyperactiv ity, and learning problems, and area was within a low disruptive behavior level for Physical problems. The average  scores for these areas are 2.05, 2.39, 2.30, 1.52 respectively and total average scores for these areas is (2.16). The findings  demonstrated a robust and positive association between the age group and disruptive behavior disorders among primary  schools’ children. However, the statistical analysis indicated that there was significant correlation between sociodemo graphic factors and DBD regarding of gender. Conclusion: In summary, students with disruptive behavioral disorders have lower academic achievement and gradu ation rates than students without disabilities. The majority of the children polled in this study reported moderate levels  of DBD.
Keywords: Disruptive Behavioral Disorders; Quality of Learning; School; Children